The Reciprocal Experience of Victims And Law Enforcement Officials Dealing With Domestic Violence Cases; Yeka Suby City, Addis Ababa, Ethiopia - Sergo, Aragaw (International Journal of Global Community, 2023)
Women have little contact with criminal justice system (CJS), and their unique circumstances and needs are overlooked by the CJS. Understanding the victim’s point of view and interactions with law enforcement officers is thus critical for developing policy, practice standards and informing professionals working in policing and the justice system. Thus, the purpose of this paper is to investigate the reciprocal experience of victims and law enforcement officials dealing with domestic violence cases; Yeka suby city, Addis Ababa, Ethiopia. The study took a qualitative approach, with data collected through in-depth interviews, key informant interview, and focus group discussion (FGD). As a result, the researcher conducted 18 interviews with police officers, victims of domestic violence, and social workers. The study found that law enforcement officials in the study area provide little or no assistance to victims of domestic violence. As a result, victims are brought into contact with the CJS when the problem is severe and/or the offense is discovered by patrol officers at a hot spot. The study also discovered that victimis are not interested to report for their victimization of domestic violence. They visit criminal justice officials in extreme situation and once the case is reported to law enforcement officials, many victims do not want their offenders prosecuted for a variety of reasons. The most important justification, as revealed by the study, is victims’ economic dependency, absence of clear victims’ protection mechanisms and policy and cultural factor where abuse of women, such as beating by intimates, is largely an accepted norm in a given community. Thus, the study recommends policy supported awareness creation for criminal justice officers, victims, offenders as well as for the community in general. Moreover, the government should have clear mechanism of supporting economic dependent victims to encourage good interaction with criminal justice officers. Finally, there should be a strategy that encourages the positive relationship between law enforcement officials and victims. Thus, there should be also victims’ protection mechanisms to build trust on CJS.